KINERJA PENYULUH PERTANIAN LAPANG (PPL) DALAM PENERAPAN PANCA USAHATANI JAGUNG SERTA HUBUNGANNYA DENGAN TINGKAT KEMAJUAN USAHATANI JAGUNG DI KECAMATAN KETAPANG KABUPATEN LAMPUNG SELATAN - Nyoman Riadi; Irwan Efendi; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The objectives of this research are to find out: the agricultural extension workers’ performance level in implementing Panca Usaha Tani (Five Principles of Agricultural Modernization Package), the level of corn farming advancement, and the correlation between Agricultural Extension Workers’ performance and the implementation of Panca Usaha Tani in corn farming, and the level of corn farming advancement in Ketapang subdistrict of South Lampung Regency.  The research data was coollected from September to October 2012. Respondents in this research were 10 Agricultural Extension Workers and 30 farmer groups that were selected purposely. The research applied a survey method and the data was analyzed by descriptive analysis and Rank Spearman’s correlation.  The results showed that the Agricultural Extension Workers’ performance level in implementing Panca Usaha Tani in corn farming was high. Agricultural Extension Workers’ performance including agricultural issues identification, work plan preparation, corn farmer groups fostering, knowledge and agricultural technology transfer were also high, yet, the cooperation of Agricultural Extension Workers with related agencies was fair. The level of corn farming advancement in Ketapang Subdistrict, South Lampung Regency was high. The indicators including income, productivity, and the use of modern input were also high overall.) There was significant  correlation between Agricultural Extension Workers’ performance with the implementation of Panca Usaha Tani in corn farming, but there was no correlation between Agricultural Extension Workers’ performance with the advancement of corn farming and the implementation of Panca Usaha Tani in corn farming with the advancement of corn farming. Key words: advancement of corn farming, agricultural extension workers, panca usaha tani